Pyrolysis kinetic parameters investigation of single and tri-component biomass: Models fitting via comparative model-free methods. (January 2022) - Phuakpunk, Kiattikhoon; Chalermsinsuwan, Benjapon; Assabumrungrat, Suttichai
Abstract: Kinetic parameters of pyrolysis reaction were important data for simulations of thermal conversion processes of biomass. This study aimed to develop a proper kinetics investigation method for the pyrolysis reaction. Here, a quasi-single reaction of pyrolysis was assumed to simplify the reactions. The model comparison among three favorite model-free methods including Ozawa-Flynn-Wall, Kissinger-Akahira-Sunose and Friedman methods, was considered. From TGA results of three biomasses, i.e., corn cob, Napier grass, and sugarcane top and leaves, they indicated that using parameters values via Friedman method in a conversion range of 0.1–0.6 could give conversion curves mostly in good agreement with experimental results when deriving them in a polynomial order of 2 (quadratic) regression model and using a reaction order of 3. Another purpose of the study was to investigate effect of mixing different biomasses on kinetics of pyrolysis reaction by plotting the parameters in a ternary diagram of tri-component biomass which was mixture of the herein biomasses. The diagram indicated that mixtures with more high-hemicellulose biomass (like corn cob) would show less activation energy in a temperature range of 220–315 °C. While mixtures with more high-cellulose biomass (like sugarcane top and leaves) would show less activation energy in a temperature range of 315–400 °C.